Successful viral suppression in a two-year-old child with human immunodeficiency virus infection treated with bictegravir/emtricitabine/tenofovir alafenamide - Coskun Ekemen; Asli Arslan; Emine Cigdem Ozer; Selda Erensoy; Zumrut Sahbudak Bal; Gulhadiye Avcu (The Turkish Journal of Pediatrics)
Background. Adherence to antiretroviral therapy (ART) is a major challenge in pediatric human immunodeficiency virus (HIV) management, especially in young children due to medication formulation, administration difficulties, and psychosocial barriers. Single-tablet regimens (STRs) have been shown to improve adherence and viral suppression in adults and adolescents, yet their use in younger children remains limited. Bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) is an STR with a high genetic barrier to resistance, making it a promising option for pediatric patients with adherence difficulties.